A combination of sbmA and tolC mutations in Escherichia coli K-12 Tn10-carrying strains results in hypersusceptibility to tetracycline - de Cristobal, Ricardo Ezequiel (2008)
Previously, we demonstrated that Escherichia coli tolC mutations reduce the high-level resistance to tetracycline afforded by the transposon Tn10-encoded TetA pump from resistance at 200 μg/ml to resistance at 40 μg/ml. In this study, we found that the addition of an sbmA mutation to a tolC::Tn10 mutant exacerbates this phenotype: the double mutant did not form colonies, even in the presence of tetracycline at a concentration as low as 5 μg/ml. Inactivation of sbmA alone partially inhibited high-level tetracycline resistance, from resistance at 200 μg/ml to resistance at 120 μg/ml. There thus appears to be an additive effect of the mutations, resulting in almost complete suppression of the phenotypic expression of Tn10 tetracycline resistance. Copyright © 2008, American Society for Microbiology. All Rights Reserved.